Analisis Kalimat pada Teks Biografi dalam Buku Cerdas Cergas Berbahasa dan Bersastra Indonesia untuk SMA/SMK Kelas X Kurikulum Merdeka (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
A grammatical arrangement has smaller constituents, namely sentences. This study aims to describe the types of sentences based on the number of clauses, modes, passive sentences, direct sentences, and negative sentences contained in the biographical text in the learning book entitled "Cerdas Cergas Berbahasa dan Bersastra Indonesia untuk SMA/SMK Kelas X Kurikulum Merdeka," which is made by Aulia & Gumilar. This article can increase knowledge about the types of sentences in the study of syntax and their application in biographical texts. The approach used in this research is a qualitative approach with a type of descriptive research. The object of the data study is in the form of sentences in four biographical texts in predetermined learning books. Data collection was carried out by determining the biographical text contained in the teaching material. Data analysis was carried out by reading each sentence in the text, analyzing the building blocks of the text, and classifying the sentences based on the types of sentences. This study uses note-taking techniques. The note-taking technique is to record the results of data analysis from sources that have been identified. The results obtained from this study show that broad sentences are more dominant than simple sentences in the types of sentences classified based on the number of clauses. Then, based on the types of sentences based on the mode, it was found that all the biographical texts contained in the learning book used declarative sentences. There were 41 types of passive sentences found in the four biographical texts analyzed. Indirect sentences totaled 3 sentences, and we found 6 negative sentences from 4 biographical texts. Based on the analysis conducted, it was found that one biographical text did not contain negative sentences and one text did not contain indirect speech.